PSYCHOLOGICAL FACTORS IN THE FORMATION OF ACADEMIC INTEGRITY IN LEGAL EDUCATION: A DEONTOLOGICAL APPROACH - Веселовська, Наталія; Павлов, Володимир (SWorldJournal, 2025)
The article examines the psychological factors of academic integrity formation in legal education in the context of the deontological approach. The relevance of the problem is determined by the fact that violations of the principles of academic integrity